Pulsed frequency modulated infrared communicator / Mohamad Naser Abdul Rahaman and Mohd. Hafizal Hamzah - Abdul Rahaman, Mohamad Naser; Hamzah, Mohd. Hafizal (2000)
Electronic communication system has developed and progressed very rapidly. It began with copper wire as the only type of link between the sender and the receiver. Later broadcasting was developed which allowed signal to be transmitted through the air (free space), without any wire. Radio transmitter used radio wave to transmit the signal, but this project Pulse-Frequency Modulated Infrared Communicator used pulsed-frequency modulated infrared which is safe to transmit voice or any signal to the receiver. Figure (a) and (b) illustrates a block diagram of the transmitter and receiver. In many situation it is impractical to used direct wiring techniques, especially when transmitter and receiver are located in placed where there are in accessible or when it is inconvenient to operate them. Infrared communicator is a useful option for short range waring from transmitter to the receiver. Infrared technology uses the atmosphere as its transmission medium and it is a practical and cost effective solution in many communication situations. This systems eliminate the need for expensive cabling and the installation challenges associated with hard wire system